Proposal of a digital image analysis method for determining the carbonated front in concretes - Silveira, Rodrigo Goettems da; Isaia, Geraldo Cechella (Ambiente Construído, 2022)
Abstract Carbonation is one of the most common pathologies in concretes and the correct determination of the depth reached by this process is essential to predict the lifespan of a structure. The most common method for measuring carbonation is to spray a phenolphthalein solution onto the concrete and then measure the colorless area of the solution. Traditionally, such measurement is done manually through visual assessment. However, as this is a subjective assessment, this process is subject to errors. In order to minimize these errors, researchers have used image editing processes and measurements obtained with computerized tools. Even using these programs, the process still depends on the operator’s sensitivity and judgment to determine the areas affected by carbonation. This work proposes a digital analysis with the assignment of phenolphthalein turning pH values in order to obtain the carbonated front limit with greater precision and in a semi-quantitative way. For this, three admixtures of concrete with pozzolans (fly ash and rice husk ash) were analyzed in binary and ternary mixtures submitted to natural carbonation. The proposed method proved to be accurate and efficient as an aid in reading carbonated depths. Resumo A carbonatação é uma das patologias mais comuns em concretos e a correta determinação da profundidade atingida por este processo é fundamental para a previsão da vida útil de uma estrutura. O método mais comum para a medição da carbonatação é a aspersão de uma solução de fenolftaleína no concreto e posterior medição da área incolor da solução. Tradicionalmente tal medida é feita manualmente através de avaliação visual. Porém, por se tratar de uma avaliação subjetiva, este processo está sujeito a erros. A fim de minimizar estes erros, pesquisadores têm usado processos de edição de imagens e medidas obtidas com ferramentas computadorizadas. Mesmo utilizando estes programas, o processo ainda depende da sensibilidade e do julgamento do operador para determinar as áreas atingidas pela carbonatação. Este trabalho propõe uma análise digital com a atribuição de valores de pH de viragem da fenolftaleína para obter-se com maior precisão e de forma semi-quantitativa o limite da frente carbonatada. Para tanto, foram analisados três traços de concreto com pozolanas (cinza volante e cinza de casca de arroz) em misturas binárias e ternária submetidos à carbonatação natural. O método proposto mostrou-se preciso e eficiente como auxiliar na leitura das profundidades carbonatadas.